PENGARUH UKURAN PERUSAHAAN, KOMPLEKSITAS OPERASI PERUSAHAAN DAN JENIS INDUSTRI TERHADAP AUDIT DELAY - Widyastuti, Made Tika; Putra Astika, Ida Bagus (E-Jurnal Akuntansi; Vol 18 No 2 (2017), 2017)
The purpose of this study was to examine the influence of the independent variables consisting of company size , the complexity of the company's operations , and the type of industry both partially and simultaneously influence audit delay . This study uses secondary data obtained from audited financial statements . The population is a company listed on the Indonesia Stock Exchange in 2011-2014 . The company in question is a banking company and the consumer goods industry . The sample selection using purposive sampling method to obtain a sample of 236 observation units in 2011-2014 . Methods of analysis tool used is multiple regression analysis . The results of this study indicate individually variable size and complexity of the company's operations affect audit delay , while industry types have no effect on audit.
Keywords: Audit delay, company size , complexity of operations of the Company and Industry Type.